PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK APRESIASI NOVEL BERBASIS PENDIDIKAN KARAKTER UNTUK PESERTA DIDIK KELAS XI SMK NEGERI SUMSEL PALEMBANG - Syilvia Novriany; Nurhayati Nurhayati; Mulyadi Eko Purnomo (Universitas Sebelas Maret, 2019)
This study aims to produce Student Worksheets with the title Appreciation Novel Based on Character Education. This research and development method modifies and collaborates the theories of the development of Gall, Gall, and Borg and the theory of development of Tessmer. Student Worksheets produced in this study through validation tests by three experts covering aspects of feasibility: material, language, presentation, and graphics. Based on the validation of the three experts, the conclusion is that the Student Worksheet is valid and worthy of being tested with revisions according to the comments and suggestions of experts. Then the Student Worksheets are tested one-to-one and small groups which result that the Student Worksheet is practical to use. The field trials were conducted through pretest and posttest, the average value of the students'novel appreciation increased from 57.07 to 82.80 (difference 25.74). Thus, the Student Worksheet Appreciation of Novel Based on Character Education is effective in improving the ability of students to appreciate the novels they read.